ANALYSIS OF NITROGEN FERTILIZER NEEDS WITH LEAF COLOR CHART AND FARMER PARTICIPATION FOR RICE PLANT (Oryza Sativa L.): ANALISIS KEBUTUHAN PUPUK NITROGEN DENGAN BAGAN WARNA DAUN DAN PARTISIPASI PETANI UNTUK TANAMAN PADI SAWAH (Oryza Sativa L.) - Achdiyat; Narita Ayu Putri (Politeknik Pembangunan Pertanian Bogor, 2022)
Farmers' participation in the analysis of nitrogen fertilizer needs with leaf color chart for Paddy (Oryza sativa L.) plants in Kec. Tambaksari Regency. Ciamis, to find out: the level of participation and factors related to farmer participation. This activity was carried out from April 22, 2019 to July 26, 2019. The variables studied in this study consisted of independent variables (farmer characteristics and the role of advisors) and the dependent variable (participation). Data was collected by filling out a questionnaire (questionnaire), interviews, and secondary data (from related institutions). The results of the analysis of farmer participation include the category of